The Potential for Natural Antioxidant Supplementation in the Early Stages of Neurodegenerative Disorders - Oppedisano, Francesca (Int J Mol Sci, 2020)
The neurodegenerative process is characterized by the progressive ultrastructural alterations of selected classes of neurons accompanied by imbalanced cellular homeostasis, a process which culminates, in the later stages, in cell death and the loss of specific neurological functions. Apart from the neuronal cell impairment in selected areas of the central nervous system which characterizes many neurodegenerative diseases (e.g., Alzheimer’s Disease, Parkinson’s Disease, Huntington’s Disease, etc.), some alterations may be found in the early stages including gliosis and the misfolding or unfolding accumulation of proteins. On the other hand, several common pathophysiological mechanisms can be found early in the course of the disease including altered oxidative metabolism, the loss of cross-talk among the cellular organelles and increased neuroinflammation. Thus, antioxidant compounds have been suggested, in recent years, as a potential strategy for preventing or counteracting neuronal cell death and nutraceutical supplementation has been studied in approaching the early phases of neurodegenerative diseases. The present review will deal with the pathophysiological mechanisms underlying the early stages of the neurodegenerative process. In addition, the potential of nutraceutical supplementation in counteracting these diseases will be assessed.